Análisis costo/beneficio de un sistema de gestión administrativa para el “Hotel Sabanetas” del cantón Montalvo - Miranda Rodriguez, Kerly Virginia (2021)
The present case study with the subject of cost / benefit analysis of an administrative management system for the Hotel Sabanetas located in the Montalvo canton, Los Ríos province, prior to obtaining the title of Systems Engineer, aims to automate the operations of the activities of the company. By implementing the software, it is intended to solve existing organizational problems, register reservations, keep track of employees, store customer information and modify reservations, it will have modules that generate billing for purchased services, reports by dates and a module of consultation of available rooms and on reservation. To be competitive in the market, it is necessary to use automated systems that help the development of the hotel, therefore, in this research project, field research was used which allowed us to obtain concrete and clear information, verifying the current situation in the administrative management of the hotel.